Radiological Findings of Malignant Tumors of External Auditory Canal. Issue 35 (September 2015) - Xia, Shuang; Yan, Shuo; Zhang, Mengjie; Cheng, Yan; Noel, Jacinth; Chong, Vincent; Shen, Wen; Raffaele, Pezzilli.
<x xml:space="preserve">Abstract</x> Abstract The primary malignant tumors of external auditory canal (EAC) are rare. The purpose of this study is to compare the imaging features of growth and recurrence pattern between 2 most common carcinomas namely squamous cell carcinoma (SCC) and adenocarcinoma of the EAC. This is a retrospective study involving 41 patients with primary EAC carcinomas of which 22 are SCC and 19 are adenocarcinoma. They were all scanned with high resolution computer tomography (HRCT) and magnetic resonance imaging. Follow-up clinical and imaging studies have also been collected and compared with a median follow-up time of 43 months (range 5–192 months). Necrosis was presented as hypodensity on computed tomography images, hyper-intense on T2WI and heterogeneous enhancement. Eighteen patients were diagnosed to be in T1 and T2 stage, it was found that SCC involved both the cartilaginous part and the bony part of the EAC (11/12), whereas adenocarcinoma involved only the cartilaginous part (6/6) (P < 0.01). Twenty-three patients were diagnosed to be in T3 and T4 stage showed bony involvement and adjacent tissue involvement for both SCC and adenocarcinoma. Parapharyngeal space involvement is much more common in recurrent SCC (P = 0.02). Lymph node metastasis was seen in 6 out of 22 patients with SCC, while 5 out of 19 patients of adenocarcinoma had lung metastasis, even at early stage (1/6; 1/5). Necrosis is more likely to occur in the patients with SCC (9/10) than that of adenocarcinoma (3/13) (P = 0.02). SCC and adenocarcinoma is seen to have different growth pattern at early stage but share similar patterns in the advanced stage. Lymph node metastasis is commonly seen in patients with SCC while adenocarcinoma shows lung metastasis even at early stage.